Effect of individualized versus standardized blood pressure management during endovascular stroke treatment on clinical outcome: a randomized clinical trial - Chen, Min; Meis, Jan; Potreck, Arne; Sauer, Lukas; Kieser, Meinhard; Bendszus, Martin; Wick, Wolfgang; Ringleb, Peter A.; Möhlenbruch, Markus Alfred; Schönenberger, Silvia (Stroke, 2023)
BACKGROUND: - Optimal blood pressure (BP) management during endovascular stroke treatment is not well established. We studied whether an individualized approach for managing BP during endovascular stroke treatment gives a better clinical outcome than an approach with standardized systolic BP targets. METHODS: The INDIVIDUATE study (Individualized Blood Pressure Management During Endovascular Treatment of Acute Ischemic Stroke Under Procedural Sedation) is a randomized clinical trial with a prospective randomized open blinded end point (PROBE) design. Patients were recruited between October 1, 2020 and July 7, 2022 at a single center at a tertiary care university hospital. Patients were eligible, when they were suffering from acute ischemic stroke of the anterior circulation with occlusions of the internal carotid artery and middle cerebral artery and a National Institutes of Health Stroke Scale score of ≥8 receiving endovascular stroke treatment in procedural sedation. The intervention consists of an individualized BP management strategy, where preinterventional baseline systolic BP (SBP) values are used as intraprocedural BP targets. As a control, the standard treatment aims to maintain the intraprocedural SBP between 140 and 180 mm Hg. The main prespecified outcome is the proportion of favorable functional outcomes 90 days after stroke, defined as a modified Rankin Scale score of 0 to 2. RESULTS: Two hundred fifty patients were enrolled and included in the analysis, mean (SD) age was 77 (12) years, 142 (57%) patients were women, and mean (SD) National Institutes of Health Stroke Scale score on admission was 17 (5.2). In all, 123 (49%) patients were treated with individualized and 127 (51%) with standard BP management. Mean (SD) intraprocedural SBP was similar in the individualized versus standard BP management group (157 [19] versus 154 [18] mm Hg; P=0.16). The rate of favorable functional outcome after 3 months was not significantly different between the individualized versus the standard BP management group (25% versus 24%; adjusted odds ratio, 0.81 [95% CI, 0.41-1.61]; P=0.56). - - CONCLUSIONS: Among patients treated with endovascular stroke treatment due to an acute ischemic stroke of the anterior circulation, no significant difference was seen between the individualized BP management strategy, where intraprocedural SBP was targeted to baseline values, and the standardized regimen of targeting SBP between 140 and 180 mm Hg. REGISTRATION: URL: https://www.clinicaltrials.gov; Unique identifier: NCT04578288.